Testing the hypoxia tolerance and hypoxic performance of fishes: A two-tier screening approach - Zhang, Yangfan; Farrell, Anthony P. (Frontiers in Marine Science, 2022)
With regional hypoxic episodes in the world’s oceans becoming more severe and more frequent, a valuable management need will be a screening protocol to characterize the full diversity of hypoxic robustness among fishes (defined here as their tolerance and performance). Yet, high-throughput screening protocols to deal with the almost 33,000 fish species have the potential to trade off convenience with the information depth normally provided with comprehensive but more time-consuming phenotyping protocols. As a solution, we propose a two-tier testing approach, one that combines a simple, rapid, cost-effective, and well-established hypoxia challenge test (a measure of hypoxic tolerance) with an individual-based hypoxic performance test that defines maximum aerobic capacity over a wide range of ambient water oxygen levels (a hypoxic performance curve). The later test would be performed on selected indicator species identified from the tolerance screening test. Here we describe the two methodological approaches for this two-tier approach using some existing data to illustrate the potential for their applications in marine science.